Inhibitory Function in Auditory Processing - Conny Kopp-Scheinpflug (Frontiers Research Topics, 2015)
There seems little doubt that from the earliest evolutionary beginnings, inhibition has been a fundamental feature of neuronal circuits - even the simplest life forms sense and interact with their environment, orienting or approaching positive stimuli while avoiding aversive stimuli. This requires internal signals that both drive and suppress behavior. Traditional descriptions of inhibition sometimes limit its role to the suppression of action potential generation. This view fails to capture the vast breadth of inhibitory function now known to exist in neural circuits. A modern perspective on inhibitory signaling comprises a multitude of mechanisms. For example, inhibition can act via a shunting mechanism to speed the membrane time constant and reduce synaptic integration time. It can act via G-protein coupled receptors to initiate second messenger cascades that influence synaptic strength. Inhibition contributes to rhythm generation and can even activate ion channels that mediate inward currents to drive action potential generation. Inhibition also appears to play a role in shaping the properties of neural circuitry over longer time scales. Experience-dependent synaptic plasticity in developing and mature neural circuits underlies behavioral memory and has been intensively studied over the past decade. At excitatory synapses, adjustments of synaptic efficacy are regulated predominantly by changes in the number and function of postsynaptic glutamate receptors. There is, however, increasing evidence for inhibitory modulation of target neuron excitability playing key roles in experience-dependent plasticity. One reason for our limited knowledge about plasticity at inhibitory synapses is that in most circuits, neurons receive convergent inputs from disparate sources. This problem can be overcome by investigating inhibitory circuits in a system with well-defined inhibitory nuclei and projections, each with a known computational function. Compared to other sensory systems, the auditory system has evolved a large number of subthalamic nuclei each devoted to processing distinct features of sound stimuli. This information once extracted is then re-assembled to form the percept the acoustic world around us. The well-understood function of many of these auditory nuclei has enhanced our understanding of inhibition's role in shaping their responses from easily distinguished inhibitory inputs. In particular, neurons devoted to processing the location of sound sources receive a complement of discrete inputs for which in vivo activity and function are well understood. Investigation of these areas has led to significant advances in understanding the development, physiology, and mechanistic underpinnings of inhibition that apply broadly to neuroscience. In this series of papers, we provide an authoritative resource for those interested in exploring the variety of inhibitory circuits and their function in auditory processing. We present original research and focused reviews touching on development, plasticity, anatomy, and evolution of inhibitory circuitry. We hope our readers will find these papers valuable and inspirational to their own research endeavors.